Impact of website quality, product assortment, customer reviews, and perceived service quality on online loyalty: the role of perceived value as a mediator - Jalal Rajeh Hanaysha; Fayez Bassam Shriedeh; Osman Gulseven (Cogent Business & Management)
The primary aim of this paper was to test the impact of customer reviews, website quality, perceived service quality, and product assortment on perceived value and online loyalty. This study also sought to confirm whether perceived value mediates the relationship among the stated factors. The required data for this research were gathered from several customers of online retail stores in the United Arab Emirates using a survey method. All responses were analyzed using the software of SmartPLS 4.0 to validate the suggested hypotheses and draw conclusions. Overall, the findings depicted that perceived value positively influences online loyalty. The outcomes also showed that customer reviews, website quality, perceived service quality, and product assortment positively affect perceived value as well as online loyalty. Finally, the outcomes support the mediating effect of perceived value among the aforementioned constructs and online loyalty. This paper contributes to the prevailing research on the topic by validating the significance of the selected factors in influencing perceived value and online loyalty, considering that only limited researches were done on these constructs in the MENA region.